Comparative Evaluation of Vildagliptin-Metformin Versus Glimepiride-Metformin on Inflammatory Markers and Glycemic Control in Type 2 Diabetes Mellitus: A Randomized, Open-Label Study - Navreet Kaur; Kanav Mehta; Sumitpal Singh Chawla (Dr. Annil Mahajan, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic disease characterized by the generation of reactive oxygen species, leading to oxidative stress and chronic low-grade inflammation. Objective: To evaluate the efficacy of the Vildagliptin-Metformin versus the Glimepiride-Metformin combination in reducing inflammatory markers and improving glycemic control in T2DM patients. Material and Methods: In this randomized, open-label, comparative study, 80 newly diagnosed T2DM patients, above 18 years of age, of either sex, with HbA1c > 6.5% [as per American Diabetes Association (ADA) criteria], were enrolled. They were divided into Group I (Vildagliptin with Metformin) and Group II (Glimepiride with Metformin). Blood samples for biochemical analysis of glycated hemoglobin (HbA1c), fasting blood glucose (FBS), Interleukin-6 (IL-6), high-sensitivity C-reactive protein (hs-CRP), and erythrocyte sedimentation rate (ESR) were collected at baseline and after 12 weeks. Results: The study found a significant reduction in hs-CRP levels in the Vildagliptin-Metformin group (41.39%) compared to the Glimepiride-Metformin group (15.69%) (p=0.001), indicating a more effective anti-inflammatory effect while maintaining comparable glycemic control. Conclusion: The Vildagliptin-Metformin combination demonstrated superior efficacy in reducing inflammation in T2DM patients, with glycemic control comparable to the Glimepiride Metformin combination. These findings suggest that Vildagliptin-Metformin could be a more effective therapeutic option for T2DM management, particularly in reducing inflammation.